Influenza vaccine uptake among older adults in Brazil: Socioeconomic equality and the role of preventive policies and public services - Ana Paula Sayuri Sato; José Leopoldo Ferreira Antunes; Maria Fernanda Furtado Lima-Costa; Fabíola Bof de Andrade (Elsevier, 2020)
Background: Influenza is a significant cause of morbidity and mortality worldwide. Since 1999, influenza vaccine is provided free-of-charge to adults aged 60 years or more in Brazil. Although vaccination coverage is high, previous studies have shown that socioeconomic and lifestyle factors play an essential role in predicting vaccine uptake. This study aimed to investigate whether previous knowledge of factors that constrain influenza vaccine uptake among older adults contributed to increasing the access to vaccination in 2015-16. Methods: This cross-sectional study assessed data from the baseline of the Brazilian Longitudinal Study of Aging. This national representative sample encompassed individuals aged 60 and older (n = 5221). Vaccination status was the outcome variable; covariates included socio-demographic and behavioral characteristics, health status, and access to healthcare. Logistic regression fitted the association between vaccine uptake and covariates. Results: The coverage of influenza vaccination was 73.0% (95% confidence interval: 70.6-75.2); ranking lower than the goal of 80% set up by the national health authority. The most frequent reasons to justify the option of skipping vaccination were cultural beliefs about the lack of efficacy and possible side effects of the vaccine. The coverage of vaccination did not differ by socioeconomic characteristics. Older individuals, never smokers, having two or more chronic diseases, and being registered in the Family Health Program were positively associated with influenza vaccine uptake. Conclusions: Absent socioeconomic inequalities point out changes in the barriers to vaccination. These findings provide insights into tailoring public health strategies, targeting professional recommendations and public perceptions of the vaccine. Keywords: Influenza vaccines, Influenza, Human, Vaccination coverage, Socioeconomic factors, Aged